2020
DOI: 10.3390/ijerph17186831
|View full text |Cite
|
Sign up to set email alerts
|

Association between Daily Activities and Behavioral and Psychological Symptoms of Dementia in Community-Dwelling Older Adults with Memory Complaints by Their Families

Abstract: It is important and useful to consider information provided by family members about individuals with memory complaints’ instrumental activities of daily living (IADL). The purpose of this study was to clarify the characteristics and relevance of individuals with memory complaints’ IADL and behavioral and psychological symptoms of dementia (BPSD) assessed from the perspective of the family members using the Process Analysis of Daily Activity for Dementia and short version Dementia Behavior Disturbance scale. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The results of this study indicated a significant decrease in BPSD for the EG and a significant increase for the CG. Similar results to these have been found in other studies [40]. There are data in the literature that support that age is positively related to increased cognitive impairment and a greater cognitive deterioration is related to a greater presence of BPSD [41], which can explain this significant increase in the control group.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study indicated a significant decrease in BPSD for the EG and a significant increase for the CG. Similar results to these have been found in other studies [40]. There are data in the literature that support that age is positively related to increased cognitive impairment and a greater cognitive deterioration is related to a greater presence of BPSD [41], which can explain this significant increase in the control group.…”
Section: Discussionsupporting
confidence: 90%
“…Reports of caregivers and especially family members on EADL have been found useful for the diagnosis of dementia. 25 Limitations of the study; activities of daily living were primarily determined using scales, therefore, in determining the ADL level, the elderly individual may have an incorrect estimation and recall bias. In future studies, the ADL challenges of elderly people with dementia living in nursing homes can be investigated with new technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Our long-term goal is to develop algorithms to identify some behavioral diseases earlier, such as Parkinson's disease, dementia, depression, and autism, by collaborating with physicians and hospitals [22][23][24][25][26][27][28]. It is also possible to employ the fast evolving large language model (LLM) and large vision model (LVM)-based AI technologies in our system.…”
Section: More Advanced Algorithmsmentioning
confidence: 99%